Practitioner Profile: An Interview with Marcee Yager, CFP - Marcee Yager (Journal of Financial Therapy, 2012)
Marcee Yager is a nationally-recognized expert in and one of the pioneers of integral planning, often called “life planning.” Integral planning combines financial analysis and advice with counseling regarding life decisions. A certified mediator and a practicing spiritual director, Marcee has been an investment advisor since 1984 and a CFP® (Certified Financial Planner) licensee since 1988. She was a participant in the initial Financial Therapy Forum and a founding member of the Financial Therapy Association. She has an extensive background in finance, strategic planning, and coaching. Her passion is enabling people to recognize the influences that affect their approach to making decisions.
Keywords: financial planning; financial therapy